(untitled) (Far Eastern Federal University: School of Engineering Bulletin, 2022)
Combination of advantages of the materials in metal-wood beams can ensure their optimal distribution over the section, which increases the overall efficiency of structures. In this work, the authors substantiate the optimal configuration of the transverse-corrugated wall profile made of prefabricated steel profiled sheets, a metal-wood I-beam. Finite element models of the investigated structures are presented, as well as the results and analysis of numerical experiments using the LIRA-SAPR software package. For the considered models of beams, forms of buckling of corrugated walls with safety factors, deformed schemes and isofields of the distribution of normal and tangential stresses are obtained.